Using pharmacists and drugstore workers as sexual healthcare givers: a qualitative study of men who have sex with men in Dar es Salaam, Tanzania - Charlotte Agardh; Felicia Weije; Anette Agardh; Joyce Nyoni; Michael W. Ross; John Kashiha; Markus Larsson (Taylor & Francis Group, 2017)
Background: Previous research has shown that men who have sex with men (MSM) avoid formal healthcare services because of the fear of discrimination as homosexuality is illegal and stigmatized in Tanzania. Instead, self-treatment by medications obtained directly from pharmacies or drugstores may be common when MSM experience symptoms of suspected sexually transmitted infections (STIs) related to sexual activity with men. Objective: To explore MSM's perceptions and experiences of seeking treatment and advice from pharmacists and drugstore workers in Dar es Salaam, Tanzania, with regards to their sexual health and STI-related problems. Materials and Methods: 15 in-depth interviews were conducted with MSM with experience of seeking assistance relating to their sexual health at pharmacies and drugstores in Dar es Salaam in 2016. A qualitative manifest and latent content analysis was applied to the collected data. Results: Four themes related to different aspects of MSM's perceptions and experiences of pharmacy care emerged from the analysis: (1) Balancing threats against need for treatment reflected informants' struggles concerning risks and benefits of seeking assistance at pharmacies and drugstores; (2) Identifying strategies to access required services described ways of approaching a pharmacist when experiencing a sexual health problem; (3) Seeing pharmacists as a first choice of care focused on informants' reasons for preferring contact with pharmacies/drugstores rather than formal healthcare services; and (4) Lacking reliable services at pharmacies indicated what challenges existed related to pharmacy care. Conclusions: MSM perceived the barriers for accessing assistance for STI and sexual health problems at pharmacies and drugstores as low, thereby facilitating their access to potential treatment. However, the results further revealed that MSM at times received inadequate drugs and consequently inadequate treatment. Multi-facetted approaches are needed, both among MSM and drugstore, pharmacy, and healthcare workers, to improve knowledge of MSM sexual health, STI treatment, and risks of antibiotic resistance.